Southeast Asian paper tigers? : from miracle to debacle and beyond - Jomo, K. S. (London ; New York : RoutledgeCurzon, 2003)
This timely and authoritative book examines and critically analyses the Southeast Asian economies over the last decade and into the future.
Includes bibliographical references and index.
rua 12/10/16
Loans
Keywords: Economic history; Economic policy; Southeast Asia